Preferences among Pregnant Women in Choosing a Private Midwife Practice as Service Provider for Antenatal Care (ANC) - Fatriani, Rully; Risneni, Risneni (Poltekkes Kemenkes Tanjung Karang, 2023)
Antenatal Care (ANC) is essential in achieving a healthy pregnancy. During the pandemic, pregnant women tended to carry out ANC in private midwife practice. The reasons for pregnant women choosing private midwife practice might differ for each individual. This study aims to describe the preference of pregnant women in choosing private midwife practice as a service provider for ANC. This research is a quantitative observational descriptive. The population was pregnant women who performed ANC at a private midwifery practice in Bandar Lampung City from June to July 2023. Eighty-eight samples obtained by accidental sampling met the inclusion criteria and expressed consent to participate. The instrument used was a questionnaire, and data was analyzed using univariate. It was found that preferences of pregnant women in choosing private midwife practice as ANC provider were more experienced midwives (27.3%), previous pregnancy history (22.7%), friendly midwives (18.2%), distance (13.6%), recommended by husband or relatives (9.1%), more affordable costs (4.5%), comfort and complete facilities (4.5%). To increase the number of ANC visits, midwives must pay attention to increasing competency in midwifery care, improving their personality, and providing the facilities pregnant women need.